Parents’ Techniques in Introducing English for Young Learner - Nurul Khairiyah; Nur Aeni; Ryan Rayhana Sofyan (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
Young students should start receiving English instruction at a young age. Parental involvement in their children's English education is crucial. By using a variety of learning approaches, parents can help their kids learn English from a young age. This study attempts to examine the methods employed by parents to start and expose their young learners to the language. Research tools in the form of interviews with 7 parents served as the data gathering strategy for this qualitative study. Several parenting strategies for teaching their kids English are categorized in this study. By using research tools in the form of interviews with 7 parents as a method of data collecting, research was carried out qualitatively. Several parenting strategies for teaching their kids English are categorized in this study. The findings indicated that parents exposed their kids to English in a variety of ways, including vocabulary introduction, the use of a vocabulary memorizing system, engaging learning techniques, and the use of learning resourcesKeywords: English fo Young Learners; Parents’Technique.